Physical properties of cassava grits before and after pneumatic drying - Romuli, S.; Abass, A.; Müller, Joachim (Wiley, 2017)
Particle characteristics are crucial knowledge to improve the process chain of cassava flour. Wet and dry grits, as the intermediate products, were investigated in this study. With respect to particle size, wet grits were predominately (66.7%) obtained between mesh size 0.50 and 1.00 mm, while dry grits (28.4%) were between 0.09 and 0.25 mm. Higher moisture content of wet grits generally resulted in higher bulk density, static and dynamic angle of repose, but lower particle density and porosity than dry grits. Plywood typically led to the highest coefficient of static friction of both, wet and dry grits. The transported mass and air velocity fitted well into a sigmoidal model. Due to particle size, terminal velocity of wet and dry grits ranged from 1.07 to 4.25 m/s and from 0.88 to 2.87 m/s, respectively, whereas conveying velocity ranged from 1.23 to 6.47 m/s and from 1.02 to 3.70 m/s.